Production of Brachiaria ruziziensis biomass fertilized with calcinated bone meal under acid treatments - Dias Damaceno, Joao Batista; Ferreira, Elvino; Oliveira, Danielle Monteiro de [UNESP]; Guimaraes, Rodrigo de Souza; Gama, Romildo Torres da; Padilha, Felipe de Jesus (Inst Federal Sul Minas Gerais-i Fsuldeminas, 2018)
With phosphorus reserves declining gradually, the interest in developing alternatives to supply the demand for fertilizers in agriculture has been increasing daily. Thus, organic residues from the slaughter of animals such as bovine bones, which are sources of phosphorus (P) and calcium (Ca), can be used for agriculture. The only impasse in its use is its low solubility and availability of plant nutrients. The objective of this study was to evaluate the productive effects of forage Brachiaria ruziziensis when submitted to fertilization with Calcinated Bone Meal (CBM) under acid treatments (10 % oxalic, 10 % acetic and 1 % hydrochloric acid, respectively). In the evaluations, the following variables were considered: fresh matter of the aerial part (MFPA) and dry matter of the aerial part (MSPA) and hydrogenation potential (pH). As standard, single superphosphate (SFS) was used for comparison. FOC acidification provided significant gains of MFPA and MSPA in the presence of 1 % HCl and Ace 10 % as extractors of P over control and FOC without the use of acids. The use of all acids in FOC provided significant increases in soil pH.
Keywords: Phosphorus; Alternative sources; Livestock waste; Forage